Effect of a Low-Dose/High-Frequency Training in Introducing a Nurse-Led Neonatal Advanced Life Support Service in a Referral Hospital in Ethiopia - Tadesse, Misrak; Hally, Suzanne; Rent, Sharla; Platt, Phillip L.; Eusterbrock, Thomas; Gezahegn, Wendmagegn; Kifle, Tsinat; Kukora, Stephanie; Pollack, Louis D. (Frontiers in Pediatrics, 2021)
Background and objective: In Ethiopia, birth asphyxia causes approximately 30% of all neonatal deaths and 11–31% of deaths among neonates delivered in healthcare facilities that have breathing difficulty at birth. This study aimed to examine the impact of low-dose, high-frequency (LDHF) training for introducing a nurse-led neonatal advanced life support (NALS) service in a tertiary care hospital in Ethiopia. Methods: Through a retrospective cohort study, a total of 12,001 neonates born post-implementation of the NALS service (between June 2017 and March 2019) were compared to 2,066 neonates born before its implementation (between June 2016 and September 2016). Based on when the neonates were born, they were divided into six groups (groups A to F). All deliveries occurred in the inpatient Labor and Delivery Unit (LDU) at St. Paul’s Hospital Millennium Medical College. The number of neonatal deaths in the LDU, neonatal intensive care unit (NICU) admission rate, and proportion of neonates with normal axillary temperature (36.5–37.5°C) within the first hour of life were evaluated. Data were analyzed using the χ2 test, and p values < 0.05 were considered statistically significant. Following the implementation of the NALS service, semi-structured interviews with key stakeholders were conducted to evaluate their perception of the service; the interviews were recorded, transcribed, and coded for thematic analysis. Results: There was a decrease in the proportion of neonates who died in the LDU (from 3.5% to 1%) during the immediate post-implementation period, followed by a sustained decrease over the study period (p < 0.001). The change in the NICU admission rate (from 22.8% to 21.2%) was insignificant (p = 0.6) during this initial period. However, this was followed by a significant sustained decrease (7.8% in group E and 9.8% in group F, p < 0.001). The proportion of newborns with normal axillary temperature improved from 46.2% during the initial post-implementation period to 87.8% (p < 0.01); this proportion further increased to 99.8%. The program was perceived positively by NALS team members, NICU care providers, and hospital administrators. Conclusion: In resource-limited settings, LDHF training for neonatal resuscitation improves the neonatal resuscitation skills and management of delivery room attendants.